Application of Games-Based Mathematics Learning in the Preschool-Elementary Transition - Eko Bayu Gumilar; Kristina Gita Permatasari (Journal of Insan Mulia Education, 2024)
The results of this study aim to understand the use of Elementary Mathematics Games in Mathematics and Science Learning for PIAUD and PGMI Study Program Students during the PAUD-SD transition period. The research design used a descriptive quantitative approach with data collection techniques through questionnaire distribution. The results of the study found that: 1) Knowledge of Elementary Mathematics Games amounted to 92%; 2) the technique of using Elementary Mathematics Games in lecture activities has increased by 85%; 3) the difficulty faced in the process of using SD Mathematics Games amounted to 80%; 4) the integration technique of SD Mathematics Games is very easy to apply in activities Mathematics and Science Learning in PIAUD and PGMI Study Programs is 90%; 5) The percentage of usefulness in the use of Elementary Mathematics Games in the Mathematics and Science Learning process in the PIAUD and PGMI Study Programs is 95% with a benefit level of 76-100%. Thus, the use of Elementary Mathematics Games can be used in developing material from teaching materials for lecturers, teachers, and students in learning process activities.